Emotions vs Colours: A Semiotics Study - Hasiana, Evelyn Theodora; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (English Department, Faculty of Humanities, Andalas University, 2024)
This study aims to determine the meaning and relationship of colourwith five human emotions in the film entitled Inside Out. Inside Out is anAmerican animated film directed by Pete Docter and produced by JonasRivera, released in 2015. The qualitative method is used to evaluate thisresearch because it can be used to focus on an interpretive, naturalisticapproach to its subject matter. The primary data is taken from the filmInside Out. Secondary data would be gathered from any sources related tosemiotics theory on the relationship between colour and human emotions,as well as to eliminate unnecessary data and solidify the research. RileyAndersen, the main character, was born in Minnesota, and the fivemanifestations of emotion in her mind are Joy (yellow), Sadness (blue),Anger (red), Disgust (green), and Fear (purple). These emotions reside inRiley’s mind’s Headquarters, where they set Riley’s state of action andturn it into a memory.Therefore, each character with a specific color ischallenging to be studied further.It begins with an overview of each colorand emotion before delving into the specifics of the relationship betweenthese emotions and the colors associated with them. This study employsRoland Barthes’ semiotic theory, which has three aspects containingdenotation, connotation, and myth, interpreting signs. To learn more, it isnecessary to dig into the changing history of society’s association of thesecolors with these five emotions. Finally, this study is hoped to inspire theanimators to use specific colors to describe the characters’ emotions.